BRAF V600E mutation in neocortical posterior temporal epileptogenic gangliogliomas. Issue 8 (August 2015) - Martinoni, Matteo; Marucci, Gianluca; de Biase, Dario; Rubboli, Guido; Volpi, Lilia; Riguzzi, Patrizia; Marliani, Federica; Toni, Francesco; Naldi, Ilaria; Bisulli, Francesca; Tinuper, Paolo; Michelucci, Roberto; et al.
Abstract The aim of this study was to verify the presence of BRAF mutations in a series of six patients affected by drug-resistant focal epilepsy associated with neocortical posterior temporal gangliogliomas (GG) who were subjected to lesionectomy between June 2008 and November 2013. GG are an increasingly recognized cause of epilepsy and represent the most common tumor in young patients undergoing surgery for intractable focal epilepsy. BRAF mutations have been identified in up to 50% of GG. Interestingly, these six patients shared a specific anatomical posterior temporal site. In all patients, histological examination confirmed the diagnosis of GG, and two were also associated with a focal cortical dysplasia (FCD) type IIa. BRAF mutations were found in four out of six GG (66.6%). Furthermore, dysplastic tissue of Patient 2 showed a concomitant BRAF V600E mutation. All patients but one (83.3%) achieved Engel Class Ia seizure control. The patient carrying a concomitant BRAF mutation in GG and FCD fell into Engel Class II. Further analyses will be required in order to better understand the meaning of BRAF mutations in epilepsy-associated tumors and FCD and their possible role as a prognostic seizure outcome and tumor behavior marker.